How do you use substitution to integrate x^2sqrt(4x+9)dx?

2 Answers
Jun 16, 2015

The answer can be written as int x^2sqrt(4x+9)\ dx=\frac{10x^2-18x+27}{140}(4x+9)^{3/2}+C

Explanation:

Use the substitution u=4x+9 so that du=4dx and x=(u-9)/4=1/4 u-9/4. Then

int x^2sqrt(4x+9)\ dx=1/4 int ((u-9)/4)^2sqrt(u)\ du

=1/64 int (u^2-18u+81)u^{1/2}\ du

=1/64 int (u^{5/2}-18u^{3/2}+81u^{1/2})\ du

=1/64*2/7 u^{7/2}-9/32*2/5 u^{5/2}+81/64*2/3 u^{3/2}+C

=(1/224 u^2-9/80 u+27/32) u^{3/2}+C

Since u^2=(4x+9)^2=16x^2+72x+81, we can write this as

=(1/14 x^2+9/28x+81/224-9/20x-81/80+27/32)(4x+9)^{3/2}+C

=\frac{10x^2-18x+27}{140}(4x+9)^{3/2}+C

Jun 17, 2015

You can rewrite this carefully.

= intx^2sqrt((2sqrtx)^2 + 3^2)dx

Now it looks like sqrt(a^2 + x^2), which resembles sqrt(1 + tan^2theta).

Let:
2sqrtx = 3tantheta
x = (9tan^2theta)/4
x^2 = (81tan^4theta)/16
sqrt((2sqrtx)^2 + 3^2) = sqrt(9tan^2theta + 9) = 3sectheta
dx = 9/4*2tanthetasec^2thetad theta = 9/2tanthetasec^2thetad theta

=> int(81tan^4theta)/16 3sectheta 9/2tanthetasec^2thetad theta

= 2187/32inttan^5thetasec^3thetad theta

Notice how that constant is irreducible... Ugh. It looks a bit crazy, but it's just large numbers. Using some identities:
= 2187/32int(sec^2theta - 1)^2sec^2thetasecthetatanthetad theta

And some u-substitution. Let:
u = sectheta
du = secthetatanthetad theta

= 2187/32int(u^2 - 1)^2u^2du

= 2187/32int(u^4 - 2u^2 + 1)u^2du

= 2187/32intu^6 - 2u^4 + u^2du

= 2187/32 (u^7/7 - 2/5u^5 + u^3/3)

= 2187/32 (sec^7theta/7 - 2/5sec^5theta + sec^3theta/3)

Draw a right triangle if you want. Since tantheta = (2sqrtx)/3, and sqrt((2sqrtx)^2 + 3^2) = sqrt(4x + 9), sectheta = sqrt(4x+9)/3:

= 2187/32 ((4x+9)^(7/2)/(7*3^7) - 2/(5*3^5)(4x+9)^(5/2) + (4x+9)^(3/2)/(3*3^3))

= 2187/32 ((4x+9)^(7/2)/(15309) - 2/(1215)(4x+9)^(5/2) + (4x+9)^(3/2)/(81))

= 1/32 ((4x+9)^(7/2)/(7) - 18/(5)(4x+9)^(5/2) + 27(4x+9)^(3/2))

= 1/32(4x+9)^(3/2)[(4x+9)^(2)/7 - 18/5(4x+9) + 27] + C

Now let's figure out how to make this look nicer. Get some common denominators, subtract in the numerator, and factor out 8/35:
= 1/32(4x+9)^(3/2)[(16x^2 + 72x + 81)/7 - 72/5x - 162/5 + 27]

= 1/32(4x+9)^(3/2)[(80x^2 + 360x + 405 - 504x - 1134 + 945)/35]

= 1/32(4x+9)^(3/2)[(80x^2 - 144x + 216)/35]

= (1*8)/(32*35)(4x+9)^(3/2)[10x^2 - 18x + 27]

= 1/140(4x+9)^("3/2")[10x^2 - 18x + 27] + C